The future of cellular industry in indonesia – ascenario planning approach - Balqis Fajarwanto, Adi; Sunitiyoso, Yos (The Indonesian Journal of Business Administration, 2018)
Abstract. Purpose : The purpose of this research is to develop possible scenarios for cellular industry in Indonesia for the next 5 years by identifying its key drivers and its key uncertainties. The possible scenarios will then used as groundwork to develop future strategy of cellular providers in Indonesia. Introduction: The telecommunications industry in Indonesia continued to experience dynamic change with intensified competitive landscape with consumer demand for data traffic grew significantly while demand for traditional legacy products –voice and SMS- declined. At the same time, cellular providers continued to experience considerable uncertainty and risk from a regulatory perspective which cellular industry hopes that the regulatory environment will continue to evolve in a direction that is supportive of future growth. Methods: This research use adaptive scenario planning with main data input are collected through interviewing expert and cellular stakeholders in Indonesia, and literature review.  Results: Four different scenarios are developed with demand and regulation become the two critical uncertainties. Narrow road, the new emerging, the declining, and the dry season are scenarios developed by combination of different situation of demand and regulation in Indonesia. For each scenario cellular providers have option and different strategy recommendation. The scenario planning approach does not aim to predict the most likely future, but to describe what could possibly and plausibly happen in the cellular industry in Indonesia, and how cellular providers might deal with the situation.  Keywords:  cellular, scenario planning, strategy, telecommunication.